TRADISI BAKAR KEMENYAN DALAM KEHIDUPAN MASYARAKAT NAGARI SABU KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Susanti, Litra; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study was conducted at Nagari Sabu Kecamatan Batipuh Kabupaten Tanah Datar. The purpose of this research is to know the fuel incenses function for the community at Nagari Sabu Kecamatan Batipuh Kabupaten Tanah Datar. The focus of this research is the implementation of the incense burning tradition in the rituals of community life at Nagari Sabu Kecamatan Batipuh Kabupaten Tanah Datar. The technique of determining samples by Purposive Sampling and determine the number of samples as many as 10 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation.Research conducted, the authors found that As a tradition, burning incense also consists of several things that must be provided. All it takes is incense and embers. Coals as a medium to burn incense are provided by the host. After the incense and embers are available, the prayer event begins. In the incense burning prayer is done after the prayer is offered in Minang or Bahasa Indonesia. Then proceed with a prayer reading by the cleric. Function of burning incense is as a spirit invite, prayer accompanist in the event selametan include aqikah prayer, death prayer, marriage prayer, prayer maulid nabi, prayer circumcision, and prayer idul fitri / idul adha and ritual treatment. Efforts to deliver and inherit the values of tradition of fuel inceses that is by passing on to the younger generation and teach it, hold studies in mosques or in mushalla. The meaning of the burning of this kemenya is to run the sunna of the Prophet. It is said sunna because the prophet and the angels are very fond of smells. One of them comes from the incense itself.Keywords: Tradition, Incense, Effort, Culture